Pengisian Family Folder Untuk Optimalisasi Kegiatan Home Visit Pasien Diabetes Mellitus Tipe II - Syahrizal, Syahrizal; Rosmanida Keumala Putri; Azzahra Humaira Fatin (Yayasan Literasi Sains Indonesia, 2024)
The existence of health services that are accessible, good quality, and answer the needs of community can improve public health. One of the programs provided by health center to resolve patient problems is the Home Visit. During the home visit, various accurate and up-to-date data will be obtained regarding the health condition of patients and family members, environmental conditions around the house, and relationships between family members. One of the supporting instruments that can be used for home visit as an effort to optimize health services is the availability of medical records in the form of a family folder. Community service activities carried out in the form of home visits to one patient with Type II Diabetes Mellitus in the working area of the Jeulingke Health Centre. Home visit activities to the preparation of reports are supervised by supervisors from the Family Medicine Department of the Faculty of Medicine, Syiah Kuala University, Banda Aceh. Home visits were carried out twice in one family. The aims are to evaluate treatment, obtain more information about the health condition of patient and family, patient-family relationship, living conditions to the environmental conditions around the patient and family members who live with the patient. Home visit activities are complemented by completing the family assessment tools which consists of a genogram, family life cycle, family map, family APGAR, family SCREEM and family life line.